Persepsi Guru Terhadap Pembelajaran Daring di SDN 001 Langgam - Marzelayani, Sri; Kurniaman, Otang; Antosa, Zariul (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
The COVID-19 pandemic has forced learning to change the way it is delivered. To prevent the spread of the virus, schools are organized with PJJ (distance learning) which is also known as online learning. Not all teachers are ready to implement because of various obstacles. This study is a qualitative research that aims to describe teachers' perceptions of online learning in elementary schools. The research subjects were teachers of grade 1, 2, 3, 4, 5 and grade 6, SDN 001 Langgam. Research data collection techniques were carried out through observation and open interviews. The data collection instrument used an observation guide and an interview guide. Data analysis used qualitative data analysis techniques proposed by Miles and Huberman. From the results of data analysis, it is known that the teacher's perception of online learning is that learning in elementary schools is not effective interms of achieving learning objectives and the learning process. Online learning burdens teachers and parents both morally and materially. Online learning makes students feel separated from their friends and students' attitudes and skills competencies are difficult to know. The success of online learning is highly dependent on the awareness and concern of parents, the availability of facilities and infrastructure, and the care of teachers.